2016
DOI: 10.1371/journal.pone.0163694
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Inhibits the Pro-Inflammatory Response and Metabolic Reprogramming in Murine Macrophages in a GPR81-Independent Manner

Abstract: Lactate is an essential component of carbon metabolism in mammals. Recently, lactate was shown to signal through the G protein coupled receptor 81 (GPR81) and to thus modulate inflammatory processes. This study demonstrates that lactate inhibits pro-inflammatory signaling in a GPR81-independent fashion. While lipopolysaccharide (LPS) triggered expression of IL-6 and IL-12 p40, and CD40 in bone marrow-derived macrophages, lactate was able to abrogate these responses in a dose dependent manner in Gpr81-/- cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 33 publications
11
113
0
4
Order By: Relevance
“…Rahman et al (24) implicated HCA2 in the differentiation of Ly6C high -positive monocytes/ macrophages into M2-like Ly6C low -positive monocytes/ macrophages in repair of ischemic damage in the brain (44). Taken together with previous results in tumor cells (41) and bone marrow-derived macrophages (40), our data suggest that lactate may promote polarization of macrophages through HCA2 activation. Interestingly, sepsis outcomes have been correlated with the M1/M2 macrophage ratio; whereas the survivors displayed a mixed M1/M2 phenotype, higher proportions of M1-macrophages or higher levels of M1-type cytokines were associated with higher mortality (45)(46)(47).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Rahman et al (24) implicated HCA2 in the differentiation of Ly6C high -positive monocytes/ macrophages into M2-like Ly6C low -positive monocytes/ macrophages in repair of ischemic damage in the brain (44). Taken together with previous results in tumor cells (41) and bone marrow-derived macrophages (40), our data suggest that lactate may promote polarization of macrophages through HCA2 activation. Interestingly, sepsis outcomes have been correlated with the M1/M2 macrophage ratio; whereas the survivors displayed a mixed M1/M2 phenotype, higher proportions of M1-macrophages or higher levels of M1-type cytokines were associated with higher mortality (45)(46)(47).…”
Section: Discussionsupporting
confidence: 82%
“…We also investigated the effect of LR treatment on inflammatory cytokine production and macrophage polarization. Lactate inhibits LPS-induced macrophage glycolysis (40) and drives tumor-associated macrophage polarization from classically activated (M1) phenotype to the alternatively activated (M2) phenotype in vivo (41). To this end, we FACS-fractionated live peritoneal cells.…”
Section: The Role Of Lactate-induced Activation Of Hca2 On Survival Imentioning
confidence: 99%
“…Cellular metabolism has emerged as a key regulator of macrophage function. Metabolic reprogramming is required to meet the bioenergetic and biosynthetic demands of the cell and to drive effector functions [8][9][10] . Alterations in metabolites and other bioactive metabolic products have also been shown to activate and regulate gene expression, signal transduction and epigenetic profiles 9,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed that lactate treatment abrogates enhanced glycolysis in TLR-stimulated macrophages, which correlates with its activity as modulator of innate response (22), Caco-2- CCL20:LUC reporter cell line was utilized to evaluate if the effects of lactate on epithelial cells could be related to metabolic changes.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that lactate impairs macrophage metabolic reprograming after LPS activation in a GPR81-independent manner (22), which has also been associated with blunting the proinflammatory cytokine response (46). In accordance with these results, Selleri et al (47) have shown that local increase of lactate in the environment of mesenchymal stromal cells shifts macrophage M1 activation toward the less inflammatory M2 (47).…”
Section: Discussionmentioning
confidence: 99%